Strategi Pengembangan Sumber Daya Manusia Untuk Meningkatkan Kinerja Karyawan Di PT Dropshipedia - Alisza Dwi Putri; Ari Susilawati; Fakhrul Arifin; Budi Ilham Maliki (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Resource development strategies can be carried out by improving quality services, increasing professional human resources, improving company performance and preserving human resources with inter-company agencies engaged in marketing. The quality of Human Resources (HR) is one of the determinants of a company's success. The need for human resources who are of course highly competent in the field of communication and information technology is increasing and in line with the convergence of communication and information flows. Data used from staff assessments and in-depth interviews with external and internal experts. The method used in this research is a qualitative method with a literature study approach. The research results showed that the Human Resources (HR) division has several priorities which are considered capable of increasing the performance and competence of the management department at PT Dropshipedia.